Implementasi RFID Mobile untuk Alat Pembayaran dan Pengontrol Keuangan Santri - Tholib Hariono; Hilyah Ashoumi (KH. A. Wahab Hasbullah University, 2020)
The Islamic boarding school is a place for students to gain religious knowledge. The Santri period is the first time for most students to fully finance independently without parental supervision. Many students are unable to help financially so that they are increasingly irrational in buying their needs, the money charts in a short time after being sent money by their parents. One of the negative impacts of uncontrolled impact is the tendency of students to inform money when they know money. This research implements RFID as a payment instrument for students in the Islamic boarding school environment, through this payment system all santri financial data can manage the good expenses owned by these students. RFID is used for several processes or needs, namely checking balances, changing pins and processing payments. The results of RFID testing show a fast time in each process, namely the balance check process which takes an average of 1.55 seconds, the process of changing pin numbers on an average of 10.05 seconds, the payment process takes an average of 4.675 seconds.